New technique of local ischemic preconditioning induction without repetitive aortic cross-clamping in cardiac surgery - Kurapeev, Dmitry I (J Cardiothorac Surg, 2015)
BACKGROUND: Several studies have demonstrated that local ischemic preconditioning can reduce myocardial ischemia–reperfusion injury in cardiac surgery patients; however, preconditioning has not become a standard cardioprotective intervention, primarily because of the increased risk of atheroembolism during repetitive aortic cross-clamping. In the present study, we aimed to describe and validate a novel technique of preconditioning induction. METHODS: Patients undergoing coronary artery bypass grafting (12 women and 78 men; mean age, 56 ± 11 years) were randomized into 3 groups: (1) Controls (n = 30), (2) Perfusion (n = 30), and (3) Preconditioning (n = 30). All patients were operated under cardiopulmonary bypass using normothermic blood cardioplegia. Preconditioning was induced by subjecting the hemodynamically unloaded heart to 2 cycles of 3 min of ischemia and 3 min of reperfusion with normokalemic blood prior to cardioplegia. In the Perfusion group, the heart perfusion remained unaffected for 12 min. Troponin I (TnI) levels were analyzed before surgery, and 12, 24, 48 h, and 7 days after surgery. The secondary endpoints included the cardiac index, plasma natriuretic peptide level, and postoperative use of inotropes. RESULTS: Preconditioning resulted in a significant reduction in the TnI level on the 7th postoperative day only (0.10 ± 0.05 and 0.33 ± 0.88 ng/ml in Preconditioning and Perfusion groups, respectively, P < 0.05). In addition, cardiac index was significantly higher in the Preconditioning group than in the Control and Perfusion groups just after weaning from cardiopulmonary bypass. The number of patients requiring inotropic support with ≥ 2 agents after surgery was significantly lower in the Preconditioning and Perfusion group than in the Control group (P < 0.05). No complications of the procedure were recorded in the Preconditioning group. CONCLUSIONS: The preconditioning procedure described can be performed safely in cardiac surgery patients. The application of this technique of preconditioning was associated with certain benefits, including improved left ventricular function after weaning from cardiopulmonary bypass and a reduced need for inotropic support. However, the infarct-limiting effect of preconditioning in the early postoperative period was not evident. The procedure does not involve repetitive aortic cross-clamping, thus avoiding possible embolic complications.